Who Should Implement Nutrition Interventions? The Application of Institutional Economics to Nutrition and the Significance of Various Constraints to the Implementation of Nutrition Interventions - Rokx, Claudia (World Bank, Washington, DC, 2013)
Much has been learned about the significance of malnutrition for individuals and for society as a whole in the past two decades. An adequately nourished population has a better chance of reaching full intellectual capacity and economic productivity and enjoying an adequate quality of life. Experience shows that nutrition interventions significantly help to reduce malnutrition but that implementing them is difficult and influenced by multiple constraints. An overview of the literature of the past two decades on implementing nutrition activities and interventions provides insights into the many factors, both positive and negative, believed to affect this process. The purpose of this paper is to analyze each factor's relative importance in the implementation of nutrition interventions. The findings of this study strongly suggest that closer attention should be paid to the factors that are significant in predicting disbursement for nutrition in World Bank projects.